2018
DOI: 10.3892/or.2018.6418
|View full text |Cite
|
Sign up to set email alerts
|

Exosome‑encapsulated microRNA‑23b as a minimally invasive liquid biomarker for the prediction of recurrence and prognosis of gastric cancer patients in each tumor stage

Abstract: Recently, exosome‑encapsulated microRNAs (miRNAs) have been attracting attention as stable and minimally invasive biomarkers in cancer patients. The aim of the present study was to clarify the value of plasma exosomal microRNA‑23b (miR‑23b) as a diagnostic and prognostic biomarker in gastric cancer (GC) patients at each tumor stage. We first selected recurrence specific exosomal miRNA by miRNA microarray from 6 GC patients (stage I) with or without recurrence, and 3 healthy volunteers. In this analysis, miR‑23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…Considering that exosomes are highly stable disease biomarkers, exo-miRNAs may be potential GC diagnostic or prognostic biomarkers that are more accurate and stable than miRNAs [26][27][28]. In order to explore whether exo-miR-15b-3p performs the above functions, we first extracted and purified exosomes from the conditioned media of three cell lines (BGC-823, SGC-7901 and GES-1) and the serum of GC patients and non-GC volunteers (n = 108, patients and volunteers as listed in Table 1).…”
Section: Serum Exo-mir-15b-3p As a Potential Gc Diagnosis And Prognosmentioning
confidence: 99%
“…Considering that exosomes are highly stable disease biomarkers, exo-miRNAs may be potential GC diagnostic or prognostic biomarkers that are more accurate and stable than miRNAs [26][27][28]. In order to explore whether exo-miR-15b-3p performs the above functions, we first extracted and purified exosomes from the conditioned media of three cell lines (BGC-823, SGC-7901 and GES-1) and the serum of GC patients and non-GC volunteers (n = 108, patients and volunteers as listed in Table 1).…”
Section: Serum Exo-mir-15b-3p As a Potential Gc Diagnosis And Prognosmentioning
confidence: 99%
“…Several reports have highlighted the clinical significance of circulating exosomal RNAs, especially miRNAs, for GC diagnosis. [7][8][9] However, the low quantity and specificity of circulating miRNAs greatly limits their value as diagnostic molecules, and other types of RNAs, such as long non-coding RNAs (lncRNAs), may be more suitable as diagnostic markers. However, the significance of cancer cell-derived exosomal lncRNA in plasma or serum for GC diagnosis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are nano-sized membrane vesicles with diameters between 30 and 100 nm (21)(22)(23). It has previously been reported that cancer-associated exosomes serve important roles in regulating the cellular functions of cancerous cells, fibroblasts, vascular smooth muscle cells and endothelial cells through effectively delivering microRNAs, mRNAs and proteins (24)(25)(26)(27)(28)(29). However, the functions of exosomes in GBM progression and radiotherapy remain unknown.…”
Section: Introductionmentioning
confidence: 99%